Conformational analysis, stereoelectronic interactions and NMR properties of 2-fluorobicyclo[2.2.1]heptan-7-ols - de Rezende, Fátima M. P.; Moreira, Marilua A.; Cormanich, Rodrigo A.; Freitas, Matheus P. (Beilstein Journal of Organic Chemistry, 2012)
Four diastereoisomers of 2-fluorobicyclo[2.2.1]heptan-7-ols were computationally investigated by using quantum-chemical calculations, and their relative energies were analyzed on the basis of stereoelectronic interactions, particularly the presence or otherwise of the F∙∙∙HO intramolecular hydrogen bond in the syn-exo isomer. It was found through NBO and AIM analyses that such an interaction contributes to structural stabilization and that the 1hJF,H(O) coupling constant in the syn-exo isomer is modulated by the nF→σ*OH interaction, i.e., the quantum nature of the F∙∙∙HO hydrogen bond.
Keywords: conformational analysis; 2-fluorobicyclo[2.2.1]heptan-7-ols; hydrogen bond; 1hJF,H(O) coupling constant; quantum-chemical calculations